Perlindungan Hak-Hak Buruh Pada Praktik Sistem Outsourcing: Sebuah Kesenjangan Penerimaan - Nafila Nafila; Erlin Kristine; Endra Wijaya (Jurnal Hukum Novelty, 2017)
Nowadays, outsourcing becomes a common system which is used in many business entities. For some reasons, as a system, outsourcing has emerged pro and contra opinions. Some people thought that outsourcing could make business run more effectively and efficiently, while the other thought that outsourcing could make labor placed in unfavorable condition. However, Indonesian law system still allows or accommodates business entities to use outsourcing in their business. In fact, through its practice, Indonesian labor law which rules outsourcing has not been implemented effectively, so the labor would become the weak party when they are in work relation with the bosses. This article will be focused on how outsourcing was implemented, and in the same situation, how the labor respond to it. This article was based on field study, in which researchers gave attention to the implementation of outsourcing system in 2 (two) different work units within the same institution, a private university in Jakarta. This study shows, because of some reasons, the labor still accepts when they were working under the outsourcing system.